MANAGEMENT OF AMLAPITTA THROUGH AHARA VIHARA AND YOGIC PRACTICES - Ruhi, *Dr; Sharma, Kavitha; Bansal, Y D (International Journal of Ayurveda and Pharma Research, 2017)
Modern eras changing lifestyle along with changing food culture has given birth to various diseases. Amlapitta is one of the most common symptom (disease) seen in the society. Hurry, Worry, and Curry are the three main reasons for the disease. The disease Amlapitta has not been mentioned in Vrihatarayee. Acharya Kashyapa was the first to describe Amlapitta as disease. Ahara is the best preventive medicine and solely responsible for health and illness, sorrow and happiness. Almost all diseases occur due to unwholesome diet and dietary habits. A good & proper diet in disease is worth a hundred medicines & no amount of medication can do well to a patient who does not follow a strict regimen of diet. Acharya Kashyap had stressed on the dietary restriction and its importance in the management of Amlapitta with utmost concern. This review paper emphasizes on strict dietary interventions and life style modifications to prevent and to cure Amlapitta as Ayurveda has given extreme importance to optimal dietary regimen and its variation as per the season, Agni, Prakriti, type of food taken and the disease condition in the management of disease like Amlapitta, where the dietary factors are working along with several other diseases, in the manifestation. Yogic practices play a significant role in the prevention & management of Amlapitta. Shatkarma detoxifies internal system and expels waste material. After completion of these Karmas there is enhancement of bodily properties.